Analysis of Failure Models and Deformation Evolution Process of Geological Hazards in Ganzhou City, China - Zhan, Qinghua; Wang, Shimei; Wang, Li; Guo, Fei; Zhao, Daipeng; Yan, Jinzhou (Frontiers in Earth Science, 2021)
In Ganzhou City, China, a complex bedrock lithology and structure, diverse topography, frequent engineering works, and abundant rainfall generate frequent, sudden, small-scale landslides that are difficult to prevent and control. This study integrates evidence data from a field investigation of landslides with geological-engineering analogues to document the distribution and development of these geohazards in Ganzhou City. Based on the distribution of landslides across different types of bedrock and soil, we identify five lithological groups prone to slope failure: granite, metamorphics (slate and phyllite), red sedimentary layers, clastic sedimentary rocks with weak interlayers, and loose Quaternary deposits. Granite and metamorphic bedrock are the two lithologies most prone to landslides. Our analysis of the genesis and mode of slope failure suggests that most landslides in Ganzhou City originated from four modes of slope failure: scouring erosion collapse, steep slope collapse, rock sliding along a rock stratum, and wedge-shaped block sliding and caving. An in-situ model test and numerical simulations were used to explore the evolution of slope deformation and failure on the most landslide-prone lithological groups, and the accumulation of debris post-failure. This work provides a reference for the assessment of the risk from, and the management of, landslide geohazards in Ganzhou City and geologically similar regions.